(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The study The development of the service quality of youth sports center bridge. The objective is to study the factors that affect the quality of the service of the youth sports center in high bridge. To study the satisfaction of youth sports center and to study the relationship between the quality of service to the satisfaction of a youth sports center in high bridge. How to study is the study of the quantitative (Quantitative research) study population is seniors who come to exercise at high bridge youth sports center. The number of people using the 323 questionnaires as a tool to study and use the data collected and processed by statistical value, the average percent tested hypothesis model (One-Way ANOVA), T-test, Correlation and Regression Analysis he study indicated that Seniors who exercise, sports center, youth bridge. Most were female, aged 60-65 years, married, graduate level education. Professional commercial business Income per month 15001-20000 baht frequency of service centers, youth sports, bridge 2-4 times a week. And at the sports center, youth Bridge over 1 hour or more different individual factors affecting customer satisfaction of service to different age and frequency of service. Different influences the satisfaction of service is different. For individual factors, gender, marital status, average income per month. Education, career, different. Affect the satisfaction of service. not different The quality of service The overall level consists of the confidence our customers. Reliability The customer response The fairness of service. The satisfaction of service. The overall level The materiality of service. Concerning use of the Service Reliability The needs The meet Providing confidence to customers. The needs The meet Providing confidence to customers. The needs The meet Providing confidence to customersThe recommendations from the study. Management should focus on improving service quality. By focusing on job performance The development of efficient services to the sports center staff. The training Authorities to supervise and advise the elderly. And to check the fitness of every month. For the safety of elderly people who use the service. And to enhance the quality of service should be assessed. The performance of the authorities seriously to build credibility and trust with seniors at the sports center bridge.